Establishment and validation of a prognostic risk model based on ADME-related genes in breast cancer - Yang, Yang; Yan, Lei; Feng, Yang; Liu, Yuling; Shi, Guangmin; Hao, Jiqing (Frontiers in Oncology, 2025)
BackgroundThe processes of absorption, distribution, metabolic action, and elimination (ADME) affect the advancement of cancer and the development of resistance to therapies. This study examined ADME-related genes in breast cancer (BRCA) mechanisms and their associations with BRCA.MethodsBRCA datasets were analyzed to identify genes with differential expression in BRCA compared to normal tissues, focusing on ADME-related genes (ADME-RGs). Stepwise regression analyses identified prognostic genes, which were used to develop a risk assessment model. BRCA patients were scored and classified into risk categories, with survival outcomes compared across groups. A predictive model incorporating key prognostic indicators estimated patient survival rates. Mechanisms were explored through enrichment analysis, immune profiling, and drug sensitivity testing. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) and western blot (WB) methodologies were employed to determine the transcription and translation levels of the six genes, with immunohistochemistry (IHC) used to validate the variations in their expression profiles.ResultsFindings indicated that six predictive genes were pinpointed which established a risk stratification model, categorizing individuals into groups with either high or low risk, whereas those in the low-risk category demonstrated improved survival outcomes. A nomogram was created for precise prediction. Analysis of enrichment pinpointed processes, including metabolism of arachidonic and fatty acids, regulation of cellular division, proteasomal activity, and breakdown of tyrosine. Immune infiltration analysis showed distinct profiles for seven cell types between risk groups. Drug sensitivity analysis revealed GW.441756, imatinib, and WH.4.023 were more effective in the low-risk group, with varying sensitivities to other drugs in the high-risk group. The qRT-PCR, WB, and IHC results matched the bioinformatics analysis, showing upregulated ATP7B expression in BRCA, indicating the high prognostic potential of the identified genes.ConclusionsADME-related prognostic genes (GSTM2, ADHFE1, ALDH2, NOS1, ATP7B, and ALDH3A1) are implicated in BRCA pathogenesis, suggesting new therapeutic strategies for BRCA treatment.